Health care regulation in America complexity, confrontation, and compromise - Field, Robert I. (New York ; Oxford : Oxford University Press, 2007)
Regulation shapes all aspects of America's fragmented health care industry. While the health and lives of patients as well as almost one-sixth of the national economy depend on its effectiveness, health care regulation in America is bewilderingly complex. 'Health Care Regulation in America' is a guide to this regulatory maze.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medical policy -- United States